2010
DOI: 10.1016/j.drugalcdep.2010.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Job loss discrimination and former substance use disorders

Abstract: Persons with former alcohol or drug use disorders are protected from labor market discrimination by the Americans with Disabilities Act of 1990. They have been neglected, however, in empirical studies of labor market discrimination following implementation of the Act. We apply econometric techniques used to study other disabled groups to determine if there are significant differences in employment outcomes for persons with and without former substance use disorders and, if so, what part of these differences po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 29 publications
(24 reference statements)
1
36
0
1
Order By: Relevance
“…This finding is consistent with previous research, which has found that alcohol use disorders are the most common co-occurring disorders among individuals with schizophrenia (Drake & Mueser, 2002). Compared to other mental health disorders, public stigma in individuals with an alcohol use disorder is high (Baldwin, Marcus, & De Simone, 2010;Schomerus, Matschinger, & Angermeyer, 2006), in part due to negative stereotypes that contribute to public perceptions of dangerousness and unpredictability (Crisp, Gelder, Goddard, & Meltzer, 2005). In the current study, alcohol severity was negatively related to self-esteem, suggesting that individuals with a co-occurring alcohol use disorder may internalize negative public opinion.…”
Section: Discussionmentioning
confidence: 98%
“…This finding is consistent with previous research, which has found that alcohol use disorders are the most common co-occurring disorders among individuals with schizophrenia (Drake & Mueser, 2002). Compared to other mental health disorders, public stigma in individuals with an alcohol use disorder is high (Baldwin, Marcus, & De Simone, 2010;Schomerus, Matschinger, & Angermeyer, 2006), in part due to negative stereotypes that contribute to public perceptions of dangerousness and unpredictability (Crisp, Gelder, Goddard, & Meltzer, 2005). In the current study, alcohol severity was negatively related to self-esteem, suggesting that individuals with a co-occurring alcohol use disorder may internalize negative public opinion.…”
Section: Discussionmentioning
confidence: 98%
“…The Americans with Disabilities Act provides some protection from discrimination for people with formerly diagnosed substance use disorders, but does not protect current users or people with a history of drug addiction who were never diagnosed with a disorder. Despite the protection of the Americans with Disabilities Act, people with former substance use disorders report greater job loss than people with no history of substance use disorders (Baldwin et al 2010). In sum, discrimination towards current and former drug users is widespread, mostly legal, and socially acceptable.…”
Section: Drug Addiction Stigma: Prejudice Stereotypes and Discriminmentioning
confidence: 99%
“…Further, stigma from work colleagues is associated with heightened stress and decreased well-being among people with other devalued marks and attributes (Earnshaw et al 2011). Workplace discrimination due to a history of drug addiction may also threaten employment status (Baldwin et al 2010) and therefore income stability which is important for MMT retention (del Rio et al 1997; Gerra et al 2003). Taken together, experiencing and anticipating prejudice, stereotypes, and discrimination from family and friends, as well as coworkers and employers may undermine mental health and MMT success among patients in addition to stigma experienced from healthcare workers.…”
Section: Experiencing Drug Addiction Stigma From Multiple Sourcesmentioning
confidence: 99%
“…[6] People with a history of substance use disorder had a higher rate of involuntary job loss in the previous year. [7] In contrast, it has been equivocally proved that retention of gainful and productive employment is an important psychosocial indicator of good prognosis in persons with substance use disorder. [8]…”
mentioning
confidence: 99%